FACTORS RELATED TO USE OF PPE IN HEALTH WORKERS OF THE IGD UNIT AT RSUD CUT NYAK DHIEN MEULABOH - Sherly Puspita Dhani; Jun Musnadi; Lili Eky Nursia N; Siti Maysaroh Fitri S (RADJA PUBLIKA, 2022)
Personal Protective Equipment (PPE) is a set of safety equipment used by workers to protect all or part of their body from the possibility of potential accidents and occupational diseases. Based on the results of a survey obtained by researchers in the field, there is data from 2020-2021, there are 52 nosocomial infection events recorded. The purpose of this study is to examine the relationship in the categories of knowledge, attitudes and compliance with the use of PPE in health workers in the IGD Unit of Cut Nyak Dhien Meulaboh Hospital. This type of research is quantitative research using cross sectional. The sample of this study used the accidental sampling method, where the researcher took a sample that happened to be found at that time amounting to 50 respondents. The results showed that there was a relationship between compliance variables (Pvalue = 0.040 and OR 0.126) with the use of PPE. However, there is no relationship of knowledge variables (Pvalue = 1.000 and OR 0.584) and attitude (Pvalue = 1.000 and OR 0.926) with the use of PPE. The conclusion of this study based on the chi-square test is that there is a relationship of compliance with the use of PPE and there is no relationship of knowledge, attitude towards the use of PPE. It is recommended to the hospital's K3 management to be able to better supervise health workers when performing medical actions to patients so that there are no health workers who do not wear PPE.